Short esophagus. Collis operation - Delgado, Bolívar; Estapé, Gonzalo (Cirugía del Uruguay, 1993)
Authors present a case of hiatus hernia and reflux esophagitis with stenosis and shortening of the esophagus which was favourably solved by a Collis-Nissen operation.